The Luis Ortega Survival Club - Reyes, Sonora (Balzer + Bray, an imprint of HarperCollins Publishers, 2023)
"Ariana Ruiz wants to be noticed. But as an autistic girl who never talks, she goes largely ignored by her peers--despite her bold fashion choices. So when cute, popular Luis starts to pay attention to her, Ari finally feels seen. Luis's attention soon turns to something more, and they have sex at a party--while Ari didn't say no, she definitely didn't say yes. Before she has a chance to process what happened and decide if she even has the right to be mad at Luis, the rumor mill begins churning--thanks, she's sure, to Luis's ex-girlfriend, Shawni. Boys at school now see Ari as an easy target, someone who won't say no. Then Ari finds a mysterious note in her locker that eventually leads her to a group of students determined to expose Luis for the predator he is. To her surprise, she finds genuine friendship among the group, including her growing feelings for the very last girl she expected to fall for. But in order to take Luis down, she'll have to come to terms with the truth of what he did to her that night--and risk everything to see justice done."--